1820: A Year of Conspiracies - Gordon Pentland (Caliban: French Journal of English Studies)
Malcolm Chase’s magisterial 1820: Disorder and Stability in the United Kingdom provided a powerful and richly contextualised account of the complex interactions of high and popular politics in a year of crisis. This article explores the ways in which conspiracy had been a key component of the politics of both governors and governed over the preceding decade and examines its rhetorical and tactical uses by radicals and by ministers. It ends by suggesting that 1820 may have been the high-water mark of conspiracy in British politics–another way in which the crucial period between the Peterloo massacre and the Queen Caroline crisis was an important turning point.